2011
DOI: 10.1097/ncc.0b013e3181e4588d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-Week Walking Program on Taiwanese Women Newly Diagnosed With Early-Stage Breast Cancer

Abstract: Nurses, depending on skill and knowledge, can encourage physical activity, refer patients to rehabilitation programs, and prescribe and monitor exercise in breast cancer population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 54 publications
0
112
1
3
Order By: Relevance
“…No previous study has examined the effects of exercise on sleep quality in patients with lymphoma. In other cancer patient groups, results have been mixed with 3 studies showing benefit (10,14,17) and 4 studies showing no benefit (12,13,15,16).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…No previous study has examined the effects of exercise on sleep quality in patients with lymphoma. In other cancer patient groups, results have been mixed with 3 studies showing benefit (10,14,17) and 4 studies showing no benefit (12,13,15,16).…”
Section: Discussionmentioning
confidence: 94%
“…The HELP Trial was powered to detect a medium standardized effect size (d) of approximately 0.50 SDs on the primary patient-reported outcome of physical functioning (17). For a power of 0.80 and 2-tailed a <0.05, 60 patients per group were required.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-two trials 30 96 two were a combination of home and centre-based training 89,93 and four were unsupervised interventions completed at home. 85,90,91,94,104 Twenty-two trials included strategies to help improve exercise adherence and support behaviour change, such Resistance NR HRmax = maximum heart rate, HR = heart rate, HRR = heart rate reserve, MET = metabolic equivalents, NR = not reported, RM repetition maximum, RPE = Rating of Perceived Exertion, VO 2max = maximum volume of oxygen consumption, VO 2peak = volume of oxygen consumption at peak exercise. a Reports data on some or all of the same participants as the study below.…”
Section: Adverse Events and Adherencementioning
confidence: 99%
“…Some previous studies supported moderate-intensity exercise possibly improving sleep quality in survivors of lung and colorectal cancer, breast cancer, 27,49 and various other cancers. 50 However, we did not observe a relationship between moderateintensity physical activity and sleep quality, but we observed that light-intensity physical activity and SOL were significantly negatively correlated (r = j0.302, P = .002).…”
Section: Predictors Of Objective Sleep Qualitymentioning
confidence: 98%